KARAKTERISTIK MINERALOGI PADA VEIN TEMBAGA KLUWIH, PACITAN, JAWA TIMUR - Verdiansyah, Okki (KURVATEK, 2023)
The southern mountains of Java are a path of copper-gold mineralization that has proven to have high economic value. Pacitan is part of the geological system and mineralization of the southern mountains, which are part of the Sunda Arc magmatism. The research area is located in the copper mining location in Kluwih village, Tulakan, Pacitan, East Java. The presence of copper mineralization in the form of massive sulfide/sulfosalt veins in the Kluwih area is evidence of an epithermal mineralization system which is rare and has not been studied intensively. This study intends to carry out mineralogical tests both physically and chemically for the characteristics and mineralogical composition of vein in the Kluwih area. The research was conducted using geological mapping methods in mine tunnels, rock sampling, laboratory analysis using petrographic methods, ore microscopy, rock geochemistry using ICP OES/MS – XRF – AAS, mineralogy using SWIR and XRD spectral analysis. The geomorphology of the Kluwih area and its surroundings consists of the morphology of alluvial plains and intrusive hills. Lithology is composed of volcanic–subvolcanic rocks in the form of porphyry dacite, dacite, dacite breccia, and alluvium. Mineralization forms in structural openings that cut and alter dacite rocks and dacite breccias. The alteration that develops in the Kluwih area, especially in the area around the mine (tunnel) is dominated by kaolinite-illite, pyrophyllite-little-sericite, chloritization, and mineralization found in the form of veins that have massive sulphide composition with the dominant internal texture being breccia. The texture or structure of the mineralization is in the form of brecciation (hydrothermal breccia), sulfide-pyrophyllite-kaolinite, quartz- sulfide/sulfosalt, and massif sulfide/sulfosalt. The results showed that the ore had a density of 4.65 gr/cm3 while the highly argillic altered side rocks had a density of 2.54 gr/cm3. In the ore, visible massive sulfide/sulfosalt minerals consist of mosaic bonds and intergrowth between similar or different minerals. The detected ore minerals are pyrite, enargite, covellite, chalcopyrite, and bornite. Enargite and pyrite are the dominant metallic minerals found in ores. Enargite crystals appear to have a size of 56 - 160µm, pyrite accumulates in anhedral crystal forms with a size of 120 - 900µm and inclusions in enargite measuring 50 - 140µm, along with covellite-chalcopyrite ± bornite minerals with a fine size of 5 - 20µm. The geochemistry of the ore is seen as sulfide filling, as evidenced by the SiO2 value of only 4.5% followed by metal enrichment in the form of 27.6% Fe, 12.6% Cu, 4.15% As, and 46.2% S. Alteration minerals which is present is probably a mica group such as phengite with a marked presence of elements of 0.7% MgO and 1.9% Al2O3. The geochemistry of the side rock is seen to have a high SiO2 value of 71.7%, followed by a high alkaline element forming alteration minerals such as pyrophyllite with an Al2O3 value of 15.3% with a low total Ca-Na-K value of 0.25%, and there is residual TiO2 by 0.38%. Terraspectral analysis and XRD confirmed that the main peaks were pyrophilite-phengite, followed by the minerals enargite and pyrite. The Kluwih vein is a copper vein associated with advanced argillic alteration, as part of a rich high sulfidation epithermal system with Cu-Au-As-Sb mineralization.